Visual inspection of acidic pH and bisulfite in white wine using a colorimetric and fluorescent probe. (15th May 2023) - Zhang, Dan; Wang, Sifan; Yang, Fangxi; Li, Zicheng; Huang, Wencai
Graphical abstract: Highlights: A bifunctional fluorescent probe Hcy-Py was designed and synthesized. Hcy-Py responded to proton and bisulfite with color and fluorescence changes. Fast visual inspection of pH and HSO3 − in white wine was achieved by paper strip. Abstract: The acidic pH and total amount of SO2 are both important quality control indexes of wine, but conventional detection techniques depend heavily on specialized instrument and professional staff, thus are not available to general customers. In this paper, a hemicyanine-based colorimetric and fluorescent probe Hcy-Py was designed and synthesized. It responded to bisulfite selectively with a LOD of 0.68 μM and responded to proton with a pKa of 3.78. Upon the treatment of solutions with different pH values and concentrations of bisulfite, the probe-loaded paper strips displayed distinct color changes under both natural light and UV lamp. When a real white wine sample was subjected to the paper strip experiment, pH as well as bisulfite concentration could be determined by naked-eye quickly and conveniently, thus a visual detection of acidic pH and bisulfite in white wine without involving any sophisticated instrument or professional skill was successfully demonstrated.